A Eulogy of Achilles - Zaborowski, Robert (Polskie Towarzystwo Filologiczne, 2023)
We often hear about Achilles’ wrath as being a central theme of the Iliad and about its destructive character. In my paper I intend to offer a different reading and to make a strong case for his outstanding personality. To do this, after an introduction, I shall, firstly, reconstruct the sequence of events relevant to Achilles’ responses, then I shall make sense of his responses and exploit them in order to set up Achilles’ internal biography. Next, I shall consider the counterfactual in the light of Aristotle’s correctness criteria for anger to see whether any better option was available to Achilles. I conclude by considering Achilles’ mental progress.